Cerebrovascular Accident in a Patient with Polycythemia: a Case Report - O. M. Drapkina; I. I. Almazova; A. V. Smirnova; S. A. Berns; R. N. Shepel (Рациональная фармакотерапия в кардиологии)
Polycythemia vera is not only a clonal disease that causes hematopoietic stem cells, but also a pathology that often leads to thrombotic complications. Thrombosis can have different localization and is clinically manifested by stroke, myocardial infarction, deep vein thrombosis of the lower extremities, pulmonary embolism, thrombosis of the veins of internal organs and other conditions. One of the most formidable thrombotic complications is acute cerebrovascular accident. The heterogeneity of the possible causes of acute cerebrovascular accident requires a careful approach to differential diagnosis for timely diagnosis and individual, pathogenetically grounded selection of means of long-term antithrombotic therapy. The presented clinical case of the development of cerebrovascular accident in a patient with polycythemia vera demonstrates the importance of an informal approach to diagnosis, as well as interdisciplinary interaction for finding the true cause of the development of acute cerebrovascular accident and the appointment of pathogenetically based treatment, aimed, among other things, at the prevention of repeated episodes of acute cerebrovascular accident and others. thrombotic complications.